Microscopic Texture of Polypropylene Fiber-Reinforced Concrete with X-Ray Computed Tomography - Yu Qin; Hua Wu; Yong Zheng; Weina Wang; Zhijian Yi (Advances in Civil Engineering)
Polypropylene fiber-reinforced concrete (PFRC) is a cement-based composite material with short-cut fibers which has been utilized to provide multidimensional reinforcement and enhance toughness of concrete. However, this improvement is closely related to the microstructural morphology of the concrete. A nondestructive technique using X-ray computed tomography (CT) was therefore used to grasp the microscopic texture of PFRC samples. The results showed that the orientation of microcracks, which appear in the interfacial transition zone, are along the surface of the coarse aggregate. The range of distribution of fibers is proportional to fiber volume fraction. The coarse aggregate influence distribution and orientation of polypropylene fibers whose shape are mainly fold line and curve. The dispersion of pores with small volume is uniform, and the distance between the pores with larger volume is short. The proportion of pores with the diameter in the range 0∼199 μm exceeds 70%, of which the sum of volume exceeds a half of total volume with the amount being about 1% of total amount.